ANALISIS PENGARUH RISIKO PEMBIAYAAN, RISIKO OPERASIONAL, DAN RISIKO LIKUIDITAS TERHADAP TINGKAT EFISIENSI PERBANKAN SYARIAH DI INDONESIA TAHUN 2013-2017 - Danar Maharudin; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2018)
Efficiency is instrument to measure bank’s performance. Efficiency of Islamic Banks  is determined by how well bankers in managing risk. This study measures efficiency level of Islamic Banks in Indonesia and the impact of financing risk, operational risk, and liquidity risk on efficiency. Efficiency is measured using Data Envelopment Analysis (DEA). The results show that efficiency level of Islamic Banks consists of : 83,3% for OTE, 92,8% for PTE, and 89,2% for SE. This result lasts for 5 years from 2013-2017. This study conducted using data from Islamic Banks that published annual report from 2013-2017. According to purposing sampling method, there are 11 Islamic Banks that meet the criteria. Data analysis method consists of : DEA Analysis, Descriptive Statistics, and Multiple Regression Analysis. The results from hypothesis test show that financing risk has negative significant impact on efficiency, operational risk has negative significant impact on efficiency, and liquidity risk has positive significant impact on efficiency level of Islamic Banks.